Effect of Antimony Content on Transition Behavior and Electric Properties of (K0.44Na0.52Li0.04)(Nb0.9−xTa0.10Sbx)O3 Ceramics - Difeo, Mauro César (2023)
Here, (K0.44Na0.52Li0.04)(Nb0.9-xTa0.1Sbx)O3 [KNL(N0.9-xTSx)] lead-free ceramics withpotential technological applications are made through B-position substitution on the perovskitestructure by Sb ions. This strategy generates crystal structure changes and stabilizes a tetragonalsymmetry, T, giving place to an orthorhombic (O–T) phase boundary close to room temperature.Specifically, our results establish that an increase in relative volume fractions of the T on the O–Tphase boundary produces an increase in functional properties. More relevantly, this improvement inproperties is accompanied by controlling the grain size. Therefore, an increase in grain size promotesthe increased domain size, favoring more domain wall motion and domain switching. Both effectsresult in an increase in the d33 coefficient. Finally, we believe this work helps to understand the factorsthat determine the improvement in the functional properties of the KNN–based piezoelectric ceramics.